Prealgebra (7th Edition)

Published by Pearson
ISBN 10: 0321955048
ISBN 13: 978-0-32195-504-3

Chapter 4 - Test: 24



Work Step by Step

$-\frac{2}{7}\times(6-\frac{1}{6})$ $=-\frac{2}{7}\times(\frac{36}{6}-\frac{1}{6})$ $=-\frac{2}{7}\times\frac{35}{6}$ $=-(\frac{2}{7}\times\frac{35}{6})$ $=-(\frac{1}{1}\times\frac{5}{3})$ $=-\frac{5}{3}$ $=-1\frac{2}{3}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.